Gramsci e a emancipação do subalterno - Del Roio, Marcos [UNESP] (FapUNIFESP (SciELO), 2007)
In his Prison Notebooks, Gramsci worked with the notion of subaltern classes and groups, a concept that has been incorporated by the Social Sciences and current Historiography. Correlatedly, problems of common sense, folklore and religion are presented. It is important to raise the question of the theoretical and political implications of Gramsci's elaborations, contextualizing them within the entirety of his theoretical and political production, even if only to contest the common uses of the concept and their real relationship to Gramsci, or to examine to what extent this author can be considered relevant for interpretations of the conditions of social struggle in contemporary capitalism. © 2008 Revista de Sociologia e Política.
Gramsci and the emancipation of the subaltern
Keywords: Antonio Gramsci; Emancipation; Subaltern classes